Cytokine inhibitory activity of eurycomanone in RAW 264.7 cells stimulated with viral-mimicking poly (I:C) - Ha Trang, Nguyen Thi; Thu Trang, Tran; Nam, Nguyen Trung (Vietnam Journal of Biotechnology, 2023)
Poly (I:C) (Polyinosinic:polycytidylic acid) is a synthetic analog of double-stranded RNA binding toll-like receptor 3 (TLR3) and mimicking a virus infection in macrophage. Here, for the first time, we showed the inhibitory effects of eurycomanone on the production of IL-6, TNF-alpha and IL-10 of RAW 264.7 cells stimulated with poly (I:C). Eurycomanone inhibited production of pro-inflammatory cytokines including IL-6 and TNF-alpha of RAW 264.7 cells stimulated with poly (I:C) with the IC50 value being 5.14 +/- 0.60 uM and 2.32 +/- 0.40 uM, respectively. Interestingly, this compound also inhibited the production of anti-inflammatory cytokine IL-10 of RAW 264.7 cells stimulated with poly (I:C) with the IC50 value being 14.60 +/- 0.32 uM. These results suggested that eurycomanone has a potentially regulatory role on production of both pro-inflammatory and anti-inflammatory cytokines in macrophage in the mimicking context of virus infection. Whether eurycomanone inhibits the binding of poly (I:C)-TLR3 or intracellular signaling pathways needs further investigation.